MULTIMODAL STORYTELLING TO IMPROVE SPEAKING SKILL OF THE NINTH GRADE STUDENTS AT SMP 9 DENPASAR - Ni Luh Putu Dian Sawitri; Luh Ketut Sri Widhiasih; Anak Agung Putu Arsana; Ni Wayan Manu Gandhi; I Kadek Dian Satriawan; Ni Luh Gede Eny Chandra (Jurnal Santiaji Pendidikan (JSP), 2025)
This classroom action research tries to improve the students’ speaking skills through the use of multimodal digital storytelling. Within several cycles, the researchers recorded students’ progress, particularly in retelling stories with the help of digital media. The subjects of this study were the ninth-grade students of SMPN 9 Denpasar. The media used differ in each cycle, making sure that students were exposed to different modality of retelling stories. After each cycle, the students were given a post-test to demonstrate their speaking skills in the form of a performance assessment. The main data was the students’ speaking scores from pre-test, post-test 1 and post-test. Another supporting data was also gathered through questionnaires to see students’ responses about the implementation of multimodal storytelling. The data was presented quantitatively with qualitative description and explanation. The result showed that there was an improvement in terms of students’ speaking scores after the implementation of multimodal storytelling. The students were also showing positive responses toward the variety of media they were being introduced to.